An assessment tool for the international healthy eating report card for preschool-aged children: a cross-cultural validation across Australia, Hong Kong, Singapore, and the United States - Wan, Alison Wing Lam; Chung, Kevin Kien Hoa; Li, Jian-Bin; Xu, Shebe Siwei; Chan, Derwin King Chung (Frontiers in Nutrition, 2024)
Objective: This study aimed to develop and validate a globally applicable assessment tool of the 43-item International Healthy Eating Report Card Scale (IHERCS) which was designed to assess preschool-aged children's eating behaviours and family home food environments (FHFEs) across different cultural settings. In particular, we examined the factor structure, internal consistency and measurement invariance of the IHERCS across four cultural samples, including Australia, Hong Kong, Singapore, and the US. Convergent and discriminant validity were then conducted.In this cross-cultural study, a total of 2059 parent-child dyads from these four regions were recruited, and the parents were asked to complete the IHERCS. An exploratory structural equational modelling approach was employed to examine two higher-order factor models of children's eating behaviours and FHFEs in the IHERCS and its cross-cultural measurement invariance.The findings demonstrated robust factor structures of the scales of children's eating behaviours and FHFEs in the IHERCS (i.e., CFI and TLI > .90; RMSEA and SRMR < .08) and an acceptable level of internal consistency (i.e., Cronbach's α = .55-.84). Full configural invariance and metric invariance were established across the four cultural contexts, but full scalar invariance was not achieved. Partial scalar invariance was found only in the scale of FHFEs. The convergent validity and discriminant validity were supported.Overall, the current findings provided preliminary support for the construct validity and measurement invariance of the IHERCS. It provides a reliable, valid and comprehensive assessment of eating behaviours and FHFEs among children in different cultural settings.